Benefits and Risks of Digital Transformation at the Firm Level: A Literature Review - Pham, Phat Tien; Nguyen, Ngoc Duc; Tran, Ba Tri (Journal of Finance - Marketing Research, 2023)
In recent years, digital transformation has gained prominence as a trending keyword in both academia and practice. Some firms have emerged as pioneers in utilizing disruptive digital technologies to enhance their performance, attracting the attention of many scholars. In this study, we aim to review and highlight the benefits and risks of digital transformation at the firm level based on existing publications. Our findings indicate three benefits: enhanced efficiency and productivity, improved customer experience, and data-driven decision-making. Additionally, we identify four risks associated with this transformation: security vulnerabilities, integration challenges, employee resistance and skill gaps, and regulatory compliance. We also provide ten recommendations for firms to select suitable digital transformation strategies based on these findings.